Influence of landscape features on spatial genetic structure of white‐tailed deer in human‐altered landscapes. Issue 2 (February 2015) - Locher, Alexandra; Scribner, Kim T.; Moore, Jennifer A.; Murphy, Brittany; Kanefsky, Jeannette
ABSTRACT: Predictive relationships between estimates of functional population connectivity and physical and biotic landscape features can provide important insights into present and future population responses to human‐mediated landscape change. Quantification of associations between landscape features and dispersal or genetic surrogates such as gene flow among areas can be particularly challenging for continuously distributed and highly mobile wildlife species. We assessed the relative influence of natural and human‐altered landscape features on white‐tailed deer ( Odocoileus virginianus ) spatial genetic structure (SGS) in southern Michigan (USA) using 7 microsatellite markers assayed for 326 adult individuals from 21 contiguous counties (33, 284 km 2 ). We used previously collected telemetry data to quantify probabilities of habitat occupancy and seasonal movements that allowed selection and weighting of landscape features to create habitat suitability indices (HSI). We assigned individuals to groups ( n  = 13) for statistical analyses quantifying relationships between measures of SGS (response variable) with Euclidean distance, least cost distances parameterized using HSI, and presence of natural (rivers) and man‐made (roads) barriers to dispersal. Over the entire study area, genetic differentiation was significant (mean F st  = 0.019, P  < 0.001) and increased with increasing inter‐group geographic distance ( r 2  = 0.381; P  < 0.05). We identified features in the landscape matrix between groups including rivers, high traffic roads, and habitats of intermediate HSI as inhibiting gene flow. Low HSI was associated with low between‐group F st and appeared to facilitate gene flow. Quantification of the relative importance of man‐made barriers (roads) and habitat suitability to SGS for white‐tailed deer emphasizes the importance of joint use of ecological and genetic analyses in conservation and control efforts for abundant and mobile wildlife species. © 2014 The Wildlife Society.